(untitled) (Comprehensive Journal of Science, 2026)
This study examines the phenomenon of repetition in Al-Rayah Al-Bayda (The White Flag) by the Libyan poet Abdulmawla Al-Baghdadi, considering it a stylistic and aesthetic device that contributes to the construction of the poetic text and deepens its semantic and psychological dimensions. The research adopts a descriptive-analytical approach, supported by stylistic analysis, to explore repetition at various levels: sound, word, phrase, and rhetorical structure. The analysis reveals that repetition is not a superficial ornamental feature, but rather an essential element closely connected to the poet’s national and emotional experience. It enhances internal rhythm, intensifies meaning, and expresses existential anxiety, protest, and a longing for peace. Repetition also guides interpretation and reinforces the national values that shape the core of the collection, making it a central structural feature in the poet’s artistic vision